Forging and heat treatment method of ZL205A alloy forge piece
By optimizing the forging and heat treatment processes, the problems of uneven microstructure, unstable mechanical properties and poor corrosion resistance of ZL205A alloy are solved, and more uniform microstructure and more stable mechanical properties are achieved, which improves the corrosion resistance and use of the alloy. life.
Patent Information
- Application Number
- CN202411257442.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
AI Technical Summary
During forging and heat treatment, ZL205A alloy is prone to problems such as uneven microstructure, unstable mechanical properties and poor corrosion resistance, which affects its service performance and life.
Adopted optimized forging and heat treatment processes, including preheating, multi-directional forging, water quenching, solution treatment and multi-stage aging hardening, control the microstructure and mechanical properties of the alloy, use precise temperature control systems and multi-directional compression to optimize the process Parameters to improve the uniformity and stability of the alloy.
It significantly improves the microstructure uniformity and mechanical properties of ZL205A alloy, enhances corrosion resistance, reduces production difficulty and cost, and extends the service life of the alloy.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of forging and heat treatment, in particular to a forging and heat treatment method for a ZL205A alloy forging. Background Art
[0002] ZL205A alloy is a high-strength, high-toughness aluminum alloy. Due to its good comprehensive properties, it is widely used in many fields such as aerospace, automobiles, machinery, etc. However, during the forging and heat treatment process of ZL205A alloy, some problems are indeed prone to occur, which have a serious impact on its performance and life.
[0003] Microstructure inhomogeneity is a common problem. During the forging process, the uneven distribution of factors such as temperature and pressure may lead to inconsistent grain size and shape inside the alloy, thus affecting its mechanical properties and corrosion resistance.
[0004] Unstable mechanical properties are also a key issue. The mechanical properties of ZL205A alloy are crucial to its application, but during forging and heat treatment, due to improper control of process parameters or the influence of other factors, the mechanical properties may fluctuate and fail to meet the requirements of practical applications.
[0005] Poor corrosion resistance should not be ignored. When ZL205A alloy is used in some harsh environments, it needs to have good corrosion resistance. However, improper operation during forging and heat treatment may cause oxidation and corrosion on the alloy surface, reducing its corrosion resistance.
[0006] In order to solve these problems, a lot of research work has been done at home and abroad, and a variety of forging and heat treatment methods of ZL205A alloy forgings have been proposed. These methods have improved the quality and performance of the alloy to a certain extent, but there are still some shortcomings.
[0007] For example, some methods are complex and require strict control of multiple process parameters, which increases production difficulty and cost. In addition, although some methods can improve the performance of alloys, the stability of the performance still needs to be improved.
[0008] Therefore, it is of great significance to further improve and perfect the forging and heat treatment methods of ZL205A alloy forgings. By optimizing process parameters and improving process flow, the uniformity of the alloy's microstructure, stability of mechanical properties and corrosion resistance can be improved to meet the needs of practical applications. This will help promote the wider application of ZL205A alloy in various fields. Summary of the invention
[0009] The object of the present invention is to provide a forging and heat treatment method of a ZL205A alloy forging to solve the problems raised in the above background technology.
[0010] To achieve the above object, the present invention provides the following technical solution: a forging and heat treatment method of a ZL205A alloy forging, characterized in that the ZL205A alloy composition includes the following raw materials in weight percentage: 5.5%-6.7% zinc, 2.0%-2.8% magnesium, 1.6%-2.3% copper, 0.5%-2% other elements, and the balance is aluminum, and the above raw materials are prepared into a ZL205A alloy billet according to proportion. The forging and heat treatment method of the ZL205A alloy forging specifically includes the following steps:
[0011] S1, preheating stage:
[0012] Preheat the ZL205A alloy billet to 420℃-460℃, and keep it warm for 1 hour for every 25mm of billet thickness to ensure uniform heating;
[0013] S2, Forging Stage:
[0014] Forging is carried out on a press equipped with a precise temperature control system, and the forging temperature is controlled at 360°C-400°C;
[0015] The deformation rate is controlled at 30%-50% to optimize the microstructure and enhance the intrinsic quality of the forging;
[0016] Implementing a multi-directional forging process to improve the anisotropy of the material and enhance its overall mechanical properties;
[0017] S3, cooling stage:
[0018] The forged material is quickly cooled to room temperature by water quenching to reduce stress concentration and avoid stress corrosion cracking;
[0019] S4. Heat treatment process:
[0020] S41.Solution treatment:
[0021] Heat the forging to 470℃-490℃ and keep it warm for 1.5-2 hours to completely dissolve all phases in the alloy;
[0022] Rapid cooling by water quenching obtains ultra-fine martensite phase, ready for age hardening;
[0023] S42. Age hardening:
[0024] The forgings are age-hardened by multi-stage age-hardening;
[0025] S5. Quality inspection.
[0026] Preferably, the other elements are any one or a combination of silicon, iron, manganese, titanium, zirconium, bismuth or tin.
[0027] Preferably, a multi-step and multi-directional forging process can significantly improve the microstructure and mechanical properties of the material, and the process is as follows:
[0028] Forging steps and directions:
[0029] Initial longitudinal compression: At the beginning of the forging process, longitudinal compression is first performed to compress the material, eliminate internal pores, and improve the microstructure;
[0030] Parameters: The deformation rate is set at 15%-20%, the heating temperature is 1200℃-1300℃, and the speed is controlled at medium to low speed;
[0031] Transverse compression: After longitudinal compression, change the direction for transverse compression to improve the isotropy of the material and further refine the grains.
[0032] Parameters: The deformation rate is increased to 20%-25%, and the heating temperature is maintained or slightly adjusted to ensure good plasticity of the material;
[0033] Oblique / angular compression: In order to adjust the lattice structure more evenly, it is achieved through oblique or angular compression. This step not only makes the plasticity of the material more evenly distributed, but also effectively controls the direction and size of the grains;
[0034] Parameters: The deformation rate at this stage is controlled at 10%-15%, and the angle of oblique compression is set between 30°-45° according to the specific material and the required finished product specifications.
[0035] Preferably, the specific steps of water quenching in S3 are: quickly reducing the high temperature on the surface of the material and gradually introducing it into the interior to reduce the overall stress and prevent cracks;
[0036] Parameters: Cooling medium: water with anti-rust additives; Temperature: 20-25℃; 30 seconds to 3 minutes depending on material thickness; Water flow: adjusted according to the size and shape of the forging to ensure full coverage.
[0037] Preferably, martensitic transformation and aging hardening are important steps in the heat treatment of steel materials, which are used to improve the hardness and strength of the materials. The specific steps are as follows:
[0038] Controlled water quenching process to form ultrafine martensite:
[0039] Use pure water or a small proportion of water-soluble coolant to ensure good heat transfer performance;
[0040] Adjust the water flow rate to 50-150 liters / minute per square meter of forging surface according to the size of the forging;
[0041] Controlling cooling rate:
[0042] The cooling rate needs to reach 100℃ / s to 500℃ / s, which is conducive to the formation of ultrafine martensitic structure;
[0043] Use temperature sensors to monitor the temperature of forgings to ensure rapid cooling from the austenite transformation zone;
[0044] Martensitic treatment:
[0045] Forgings need to be completely cooled to room temperature (22-25°C), and temperature sensors are used to ensure compliance;
[0046] Examine the cross section of the forging under a microscope to observe whether the microstructure of the martensite is uniform and refined.
[0047] Preferably, the specific steps of aging hardening are as follows:
[0048] Carry out primary aging, keep at 120℃-140℃ for 6-8 hours, and achieve over-aging to eliminate residual stress in forgings;
[0049] Then carry out secondary aging, keep the forging at 160℃-180℃ for 10-12 hours to improve hardness and strength;
[0050] The temperature is finally raised to 190°C-210°C and kept at this temperature for 2-3 hours to optimize the tensile strength and ductility ratio of the alloy.
[0051] Preferably, the quality inspection includes:
[0052] Mechanical properties test: including tensile strength, elongation and yield strength test;
[0053] Microstructural analysis: Alloy microstructure was evaluated using scanning electron microscopy and transmission electron microscopy;
[0054] Corrosion resistance test: salt spray test and corrosion rate test are carried out to verify the corrosion resistance of the alloy. The forging and heat treatment method of a ZL205A alloy forging proposed in the present invention has the following beneficial effects:
[0055] 1. Significantly improve the uniformity of the microstructure of ZL205A alloy forgings, giving them better mechanical properties and corrosion resistance: By optimizing the forging and heat treatment processes, the crystallization process of the alloy can be controlled to make the grains finer and more uniform. This helps to improve the mechanical properties of the alloy, such as strength, toughness and hardness, while also enhancing its corrosion resistance. Uniform microstructure can reduce internal defects and stress concentration, and improve the reliability and service life of the alloy.
[0056] 2. Optimize forging and heat treatment processes, reduce production difficulty and cost: The patented method improves and optimizes the traditional process, simplifies the process flow, and reduces unnecessary steps and operations. This helps to reduce production difficulty, improve production efficiency, and also reduce production costs. The optimized process can also reduce energy consumption and material waste, further improving the economic efficiency of production.
[0057] 3. Improved the stability of the alloy's mechanical properties, ensuring its reliability in practical applications: Stable mechanical properties are a key requirement for alloys in practical applications. By optimizing the process, the alloy's mechanical properties can be made more stable and performance fluctuations can be reduced. This helps ensure that the alloy can maintain good performance under different working conditions, improving its reliability and safety.
[0058] 4. Enhanced corrosion resistance of the alloy and extended its service life: Corrosion resistance is an important property of alloys used in harsh environments. By optimizing the process, the surface state of the alloy can be improved, forming a denser oxide film or coating, and improving its corrosion resistance. This helps to extend the service life of the alloy and reduce maintenance and replacement costs.
[0059] In summary, the beneficial effects of this patent include improving microstructure uniformity, optimizing process, improving mechanical property stability, enhancing corrosion resistance and wide applicability. These effects will help improve the quality and performance of ZL205A alloy forgings, meet the needs of practical applications, and be widely used in related fields. DETAILED DESCRIPTION
[0060] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0061] The invention provides a technical solution: a forging and heat treatment method of a ZL205A alloy forging, wherein the ZL205A alloy composition comprises the following raw materials in weight percentage: 5.5%-6.7% zinc, 2.0%-2.8% magnesium, 1.6%-2.3% copper, 0.5%-2% other elements, and the balance is aluminum, wherein the other elements are any one or a combination of several of silicon, iron, manganese, titanium, zirconium, bismuth or tin, and the above raw materials are prepared into a ZL205A alloy blank according to a proportion, and the forging and heat treatment method of the ZL205A alloy forging specifically comprises the following steps:
[0062] S1, preheating stage:
[0063] Preheat the ZL205A alloy billet to 420℃-460℃, and keep it warm for 1 hour for every 25mm of billet thickness to ensure uniform heating.
[0064] S2, Forging Stage:
[0065] Forging is carried out on a press equipped with a precise temperature control system, and the forging temperature is controlled at 360°C-400°C;
[0066] The deformation rate is controlled at 30%-50% to optimize the microstructure and enhance the intrinsic quality of the forging;
[0067] Implementing a multi-directional forging process to improve the anisotropy of the material and enhance its overall mechanical properties;
[0068] The process is as follows:
[0069] Forging steps and directions:
[0070] Initial longitudinal compression: At the beginning of the forging process, longitudinal compression is first performed to compress the material, eliminate internal pores, and improve the microstructure;
[0071] Parameters: The deformation rate is set at 15%-20%, the heating temperature is 1200℃-1300℃, and the speed is controlled at medium to low speed;
[0072] Transverse compression: After longitudinal compression, change the direction for transverse compression to improve the isotropy of the material and further refine the grains.
[0073] Parameters: The deformation rate is increased to 20%-25%, and the heating temperature is maintained or slightly adjusted to ensure good plasticity of the material;
[0074] Oblique / angular compression: In order to adjust the lattice structure more evenly, it is achieved through oblique or angular compression. This step not only makes the plasticity of the material more evenly distributed, but also effectively controls the direction and size of the grains;
[0075] Parameters: The deformation rate at this stage is controlled at 10%-15%, and the angle of oblique compression is set between 30°-45° according to the specific material and the required finished product specifications.
[0076] S3, cooling stage:
[0077] The forged material is quickly cooled to room temperature by water quenching to reduce stress concentration and avoid stress corrosion cracking;
[0078] Rapidly reduce the high temperature on the material surface and gradually introduce it into the interior to reduce overall stress and prevent cracks;
[0079] Parameters: Cooling medium: water with anti-rust additives; Temperature: 20-25℃; 30 seconds to 3 minutes depending on material thickness; Water flow: adjusted according to the size and shape of the forging to ensure full coverage.
[0080] S4. Heat treatment process:
[0081] S41.Solution treatment:
[0082] Heat the forging to 470℃-490℃ and keep it warm for 1.5-2 hours to completely dissolve all phases in the alloy;
[0083] Rapid cooling by water quenching obtains ultra-fine martensite phase, ready for age hardening;
[0084] Martensitic transformation and aging hardening are important steps in the heat treatment of steel materials, which are used to improve the hardness and strength of the materials. The specific steps are as follows:
[0085] Controlled water quenching process to form ultrafine martensite:
[0086] Use pure water or a small proportion of water-soluble coolant to ensure good heat transfer performance;
[0087] Adjust the water flow rate to 50-150 liters / minute per square meter of forging surface according to the size of the forging;
[0088] Controlling cooling rate:
[0089] The cooling rate needs to reach 100℃ / s to 500℃ / s, which is conducive to the formation of ultrafine martensitic structure;
[0090] Use temperature sensors to monitor the temperature of forgings to ensure rapid cooling from the austenite transformation zone;
[0091] Martensitic treatment:
[0092] Forgings need to be completely cooled to room temperature (22-25°C), and temperature sensors are used to ensure compliance;
[0093] Examine the cross section of the forging under a microscope to observe whether the microstructure of the martensite is uniform and refined.
[0094] S42. Age hardening:
[0095] The forgings are age-hardened by multi-stage age-hardening;
[0096] Carry out primary aging, keep at 120℃-140℃ for 6-8 hours, and achieve over-aging to eliminate residual stress in forgings;
[0097] Then carry out secondary aging, keep the forging at 160℃-180℃ for 10-12 hours to improve hardness and strength;
[0098] The temperature is finally raised to 190°C-210°C and kept at this temperature for 2-3 hours to optimize the tensile strength and ductility ratio of the alloy.
[0099] S5. Quality inspection;
[0100] Mechanical properties test: including tensile strength, elongation and yield strength test;
[0101] Microstructural analysis: Alloy microstructure was evaluated using scanning electron microscopy and transmission electron microscopy;
[0102] Corrosion resistance test: Salt spray test and corrosion rate test are carried out to verify the corrosion resistance of the alloy.
[0103] Embodiment 1:
[0104] A forging and heat treatment method for a ZL205A alloy forging, wherein the ZL205A alloy composition includes the following raw materials in weight percentage: 5.5% zinc, 2.0% magnesium, 1.6% copper, 0.5% other elements, the balance being aluminum, and the other elements being several combinations of silicon, iron, and manganese. The above raw materials are prepared into a ZL205A alloy blank according to proportions, comprising the following steps:
[0105] 1. Preheating stage: Preheat the ZL205A alloy billet to 420℃, and keep it warm for 1 hour for every 25mm of billet thickness.
[0106] 2. Forging stage: Forging is carried out on a press equipped with a precise temperature control system, and the forging temperature is controlled at 360°C; the deformation rate is controlled at 30% to optimize the microstructure and enhance the intrinsic quality of the forging; a multi-directional forging process is implemented to improve the anisotropy of the material and enhance its overall mechanical properties.
[0107] 3. Cooling stage: The forged material is quickly cooled to room temperature by water quenching to reduce stress concentration and avoid the occurrence of stress corrosion cracks.
[0108] 4. Heat treatment process:
[0109] Solution treatment: Heat the forging to 470°C and keep it at this temperature for 1.5 hours to completely dissolve the various phases in the alloy; then perform water quenching and rapid cooling to obtain an ultra-fine martensite phase, in preparation for aging hardening.
[0110] Age hardening: The forgings are age hardened by multi-stage age hardening; primary aging is carried out at 120°C for 6 hours to achieve over-aging to eliminate residual stress in the forgings; secondary aging is carried out at 160°C for 10 hours to increase hardness and strength; finally the temperature is raised to 190°C and kept for 2 hours to optimize the alloy's tensile strength and ductility ratio.
[0111] 5. Quality inspection: Mechanical property tests include tensile strength, elongation, and yield strength tests; microstructural analysis uses scanning electron microscopy and transmission electron microscopy to evaluate the alloy microstructure; corrosion resistance tests conduct salt spray tests and corrosion rate tests to verify the corrosion resistance of the alloy.
[0112] Mechanical properties test:
[0113] Tensile strength: 520MPa;
[0114] Elongation: 12%;
[0115] Yield strength: 450MPa;
[0116] Microstructure analysis:
[0117] Scanning electron microscopy: fine and uniform grain structure was observed;
[0118] Transmission electron microscopy: It was found that there was a dispersed strengthening phase in the alloy;
[0119] Corrosion resistance test:
[0120] Salt spray test: After 500 hours of salt spray test, there is no obvious corrosion on the surface;
[0121] Corrosion rate: The corrosion rate is 0.05mm / year.
[0122] Embodiment 2:
[0123] A forging and heat treatment method for a ZL205A alloy forging, wherein the ZL205A alloy composition comprises the following raw materials in weight percentage: 6.7% zinc, 2.8% magnesium, 2.3% copper, 2% other elements, and the balance is aluminum, and the other elements are several combinations of silicon, iron, manganese, titanium, and zirconium. The above raw materials are prepared into a ZL205A alloy blank according to proportion, comprising the following steps:
[0124] 1. Preheating stage: Preheat the ZL205A alloy billet to 440℃, and keep it warm for 1 hour for every 25mm of billet thickness.
[0125] 2. Forging stage: Forging is carried out on a press equipped with a precise temperature control system, and the forging temperature is controlled at 380°C; the deformation rate is controlled at 40% to optimize the microstructure and enhance the intrinsic quality of the forging; a multi-directional forging process is implemented to improve the anisotropy of the material and enhance its overall mechanical properties.
[0126] 3. Cooling stage: The forged material is quickly cooled to room temperature by water quenching to reduce stress concentration and avoid the occurrence of stress corrosion cracks.
[0127] 4. Heat treatment process:
[0128] Solution treatment: Heat the forging to 480°C and keep it at this temperature for 1.8 hours to completely dissolve the various phases in the alloy; then perform water quenching and rapid cooling to obtain an ultra-fine martensite phase, in preparation for aging hardening.
[0129] Age hardening: The forgings are age hardened by multi-stage age hardening; primary aging is carried out at 130°C for 7 hours to achieve over-aging to eliminate residual stress in the forgings; secondary aging is carried out at 170°C for 11 hours to increase hardness and strength; finally the temperature is raised to 200°C and kept for 2.5 hours to optimize the alloy's tensile strength and ductility ratio.
[0130] 5. Quality inspection: Mechanical property tests include tensile strength, elongation, and yield strength tests; microstructural analysis uses scanning electron microscopy and transmission electron microscopy to evaluate the alloy microstructure; corrosion resistance tests conduct salt spray tests and corrosion rate tests to verify the corrosion resistance of the alloy.
[0131] Mechanical properties test:
[0132] Tensile strength: 540MPa;
[0133] Elongation: 13%;
[0134] Yield strength: 460MPa;
[0135] Microstructure analysis:
[0136] Scanning electron microscopy: shows a finer grain structure;
[0137] Transmission electron microscopy: It was observed that the distribution of the strengthening phase was more uniform;
[0138] Corrosion resistance test:
[0139] Salt spray test: After 550 hours of salt spray test, the surface is only slightly corroded;
[0140] Corrosion rate: The corrosion rate is 0.04mm / year.
[0141] Embodiment 3:
[0142] A forging and heat treatment method for a ZL205A alloy forging, wherein the ZL205A alloy composition comprises the following raw materials in weight percentage: 6% zinc, 2.5% magnesium, 2% copper, 1% other elements, and the balance is aluminum, wherein the other elements are several combinations of silicon, iron, manganese, titanium, and zirconium, and the above raw materials are prepared into a ZL205A alloy blank according to proportion, comprising the following steps:
[0143] 1. Preheating stage: Preheat the ZL205A alloy billet to 460℃, and keep it warm for 1 hour for every 25mm of billet thickness.
[0144] 2. Forging stage: Forging is carried out on a press equipped with a precise temperature control system, and the forging temperature is controlled at 400°C; the deformation rate is controlled at 50% to optimize the microstructure and enhance the intrinsic quality of the forging; a multi-directional forging process is implemented to improve the anisotropy of the material and enhance its overall mechanical properties.
[0145] 3. Cooling stage: The forged material is quickly cooled to room temperature by water quenching to reduce stress concentration and avoid the occurrence of stress corrosion cracks.
[0146] 4. Heat treatment process:
[0147] Solution treatment: Heat the forging to 490°C and keep it for 2 hours to completely dissolve the various phases in the alloy; then quickly cool it by water quenching to obtain an ultra-fine martensite phase, preparing for aging hardening.
[0148] Age hardening: The forgings are age hardened by multi-stage age hardening; primary aging is carried out at 140°C for 8 hours to achieve over-aging to eliminate residual stress in the forgings; secondary aging is carried out at 180°C for 12 hours to increase hardness and strength; finally the temperature is raised to 210°C and kept for 3 hours to optimize the alloy's tensile strength and ductility ratio.
[0149] 5. Quality inspection: Mechanical property tests include tensile strength, elongation, and yield strength tests; microstructural analysis uses scanning electron microscopy and transmission electron microscopy to evaluate the alloy microstructure; corrosion resistance tests conduct salt spray tests and corrosion rate tests to verify the corrosion resistance of the alloy.
[0150] Mechanical properties test:
[0151] Tensile strength: 560MPa;
[0152] Elongation: 14%;
[0153] Yield strength: 470MPa;
[0154] Microstructure analysis:
[0155] Scanning electron microscope: It shows an extremely fine equiaxed crystal structure;
[0156] Transmission electron microscopy: The quantity and distribution of the strengthening phase are further optimized;
[0157] Corrosion resistance test:
[0158] Salt spray test: After 600 hours of salt spray test, the surface is almost corrosion-free;
[0159] Corrosion rate: The corrosion rate is 0.03mm / year.
[0160] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A forging and heat treatment method for a ZL205A alloy forging, characterized in that: The ZL205A alloy composition includes the following raw materials in weight percentage: 5.5%-6.7% zinc, 2.0%-2.8% magnesium, 1.6%-2.3% copper, 0.5%-2% other elements, and the balance is aluminum. The above raw materials are prepared into ZL205A alloy billets according to the proportions. The forging and heat treatment method of ZL205A alloy forgings specifically includes the following steps: S1, preheating stage: Preheat the ZL205A alloy billet to 420℃-460℃, and keep it warm for 1 hour for every 25mm of billet thickness to ensure uniform heating; S2, Forging Stage: Forging is carried out on a press equipped with a precise temperature control system, and the forging temperature is controlled at 360°C-400°C; The deformation rate is controlled at 30%-50% to optimize the microstructure and enhance the intrinsic quality of the forging; Implementing a multi-directional forging process to improve the anisotropy of the material and enhance its overall mechanical properties; S3, cooling stage: The forged material is quickly cooled to room temperature by water quenching to reduce stress concentration and avoid stress corrosion cracking; S4. Heat treatment process: S41.Solution treatment: Heat the forging to 470℃-490℃ and keep it warm for 1.5-2 hours to completely dissolve all phases in the alloy; Rapid cooling by water quenching obtains ultra-fine martensite phase, ready for age hardening; S42. Age hardening: The forgings are age-hardened by multi-stage age-hardening; S5. Quality inspection.
2. The forging and heat treatment method of a ZL205A alloy forging according to claim 1, characterized in that: The other elements are any one or a combination of silicon, iron, manganese, titanium, zirconium, bismuth or tin.
3. The forging and heat treatment method of a ZL205A alloy forging according to claim 2, characterized in that: The microstructure and mechanical properties of the material can be significantly improved by using a multi-step and multi-directional forging process as follows: Forging steps and directions: Initial longitudinal compression: At the beginning of the forging process, longitudinal compression is first performed to compress the material, eliminate internal pores, and improve the microstructure; Parameters: The deformation rate is set at 15%-20%, the heating temperature is 1200℃-1300℃, and the speed is controlled at medium to low speed; Transverse compression: After longitudinal compression, change the direction for transverse compression to improve the isotropy of the material and further refine the grains. Parameters: The deformation rate is increased to 20%-25%, and the heating temperature is maintained or slightly adjusted to ensure good plasticity of the material; Oblique / angular compression: In order to adjust the lattice structure more evenly, it is achieved through oblique or angular compression. This step not only makes the plasticity of the material more evenly distributed, but also effectively controls the direction and size of the grains; Parameters: The deformation rate at this stage is controlled at 10%-15%, and the angle of oblique compression is set between 30°-45° according to the specific material and the required finished product specifications.
4. The forging and heat treatment method of a ZL205A alloy forging according to claim 3, characterized in that: The specific steps of water quenching in S3 are: quickly reduce the high temperature on the surface of the material and gradually introduce it into the interior to reduce the overall stress and prevent cracks; Parameters: Cooling medium: water with anti-rust additives; Temperature: 20-25℃; 30 seconds to 3 minutes depending on material thickness; Water flow: adjusted according to the size and shape of the forging to ensure full coverage.
5. The forging and heat treatment method of a ZL205A alloy forging according to claim 4, characterized in that: Martensitic transformation and aging hardening are important steps in the heat treatment of steel materials, which are used to improve the hardness and strength of the materials. The specific steps are as follows: Controlled water quenching process to form ultrafine martensite: Use pure water or a small proportion of water-soluble coolant to ensure good heat transfer performance; Adjust the water flow rate to 50-150 liters / minute per square meter of forging surface according to the size of the forging; Controlling cooling rate: The cooling rate needs to reach 100℃ / s to 500℃ / s, which is conducive to the formation of ultrafine martensitic structure; Use temperature sensors to monitor the temperature of forgings to ensure rapid cooling from the austenite transformation zone; Martensitic treatment: Forgings need to be completely cooled to room temperature (22-25°C), and temperature sensors are used to ensure compliance; Examine the cross section of the forging under a microscope to observe whether the microstructure of the martensite is uniform and refined.
6. The forging and heat treatment method of a ZL205A alloy forging according to claim 5, characterized in that: The specific steps of age hardening are as follows: Carry out primary aging, keep at 120℃-140℃ for 6-8 hours, and achieve over-aging to eliminate residual stress in forgings; Then carry out secondary aging, keep the forging at 160℃-180℃ for 10-12 hours to improve hardness and strength; The temperature is finally raised to 190°C-210°C and kept at this temperature for 2-3 hours to optimize the tensile strength and ductility ratio of the alloy.
7. The forging and heat treatment method of a ZL205A alloy forging according to claim 6, characterized in that: Quality inspection includes: Mechanical properties test: including tensile strength, elongation and yield strength test; Microstructural analysis: Alloy microstructure was evaluated using scanning electron microscopy and transmission electron microscopy; Corrosion resistance test: Salt spray test and corrosion rate test are carried out to verify the corrosion resistance of the alloy.
